Molluscicidal Screening of Hypocreales Fungi from a Brazilian Cerrado Cave Against Biomphalaria glabrata Snails - Dominnyke Slater Santos Neves; Cyntia Ayumi Yokota Harayashiki; Pedro Henrique Félix de Oliveira; Thiago Lopes Rocha; Jadson Diogo Pereira Bezerra (Journal of Fungi)
Fungi play vital roles in ecosystems through parasitism, commensalism, and mutualism. Additionally, they are widely used in industry as bioactive compound producers and biological control agents. Biomphalaria glabrata is a freshwater snail often controlled with chemical molluscicides. However, developing effective alternatives to these chemical treatments is essential. This study evaluated the molluscicidal potential of culture supernatant from Hypocreales fungi isolated from a cave in the Brazilian Cerrado against the B. glabrata. The isolates were identified based on morphological features and ITS rDNA sequences. Fifteen filtrates of Hypocreales fungi were obtained and tested both pure and in different dilutions (10% and 50%) against newly hatched snails during 96 h of exposure. The fungal isolates were identified as belonging to the genera of Clonostachys (1), Cylindrocladiella (1), Fusarium (1), Gliocladiopsis (1), Keithomyces (1), Marquandomyces (1), Ovicillium (1), Pochonia (1), Purpureocillium (1), Sarcopodium (1), Sarocladium (1), Trichoderma (3), and Volutella (1). The results showed 93.33% (14) of the fungal filtrates induced significant mortality, indicating their molluscicidal activity, with Pochonia chlamydosporia FCCUFG 100 and Volutella aeria FCCUFG 107 causing 100% mortality in all dilutions. These results reveal the potential of Hypocreales fungi from a Brazilian Cerrado cave as a promising approach for snail control.